Perspectives on Practice: ‘What will the outcome of Outcomes-Based Accountability be for Northern Ireland’s arts and cultural organisations?’ - Henry, Margaret (Irish Journal of Arts Management and Cultural Policy, 2019)
The first piece for Perspectives in Practice, Margaret Henry of Thrive examines the implications, challenges and potential benefits of the introduction of an Outcomes-Based Accountability approach to government planning by the Northern Ireland Executive. Prior to its collapse, the Executive of the Northern Ireland Assembly was about to sign off a new Programme for Government (PfG). A fundamental change to previous government planning is the adoption of an Outcomes-based Accountability® or OBA approach to measurement, developed by Mark Friedman (1). The process of developing and implementing this new process has encountered a number of problems and some would argue is flawed in its approach. This has led to much confusion in government, and between government and the voluntary and cultural sectors, in particular around co-design, one of its underpinning principles. In this, the Irish Journal of Arts Management and Cultural Policy’s first piece for ‘Perspectives in Practice’, Margaret Henry attempts to unpick some of the pitfalls and challenges of this approach. She considers what this approach is and means for the arts and cultural sector strategically, operationally, and as a fundamental planning and evaluation tool for the future. Since 2015, Henry has been part of the Arts Collaboration Network, an informal voluntary group of cultural organisations working with Community Evaluation Northern Ireland on how the cultural sector might respond to this new approach through adopting a ‘Theory of Change’ model of impact planning. In this article, she draws on her most recent work as CEO of Thrive to look at how the organisation has grappled with introducing a Theory of Change approach.